2001
DOI: 10.1002/ar.1168
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and differentiation in a model of human skin equivalent

Abstract: Recent advances in culturing technology has permitted the production of organotypic models that may be referred to as human skin equivalents (HSE). We have studied histochemical, ultrastructural, and kinetic aspects of an HSE composed by an epidermal equivalent and a dermal equivalent separated by a basement membrane. Only keratinocytes and fibroblasts were present in the epidermal and dermal equivalents, respectively; cells of other lineages were lacking. Keratinocyte stratification and differentiation seemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Our findings are in accordance with previous studies showing that the formation of basement membrane at the dermal-epidermal junction, as well as the synthesis of other matrices by dermal fibroblasts, requires the interactions between keratinocytes and dermal fibroblasts. [43][44][45]57 Although the basement membrane was absent in our constructs, basal keratinocytes expressed integrin b1 subunit and a2b1 integrin. Integrins are heterodimeric cellsurface glycoproteins that primarily mediate the attachment of basal keratinocyte to extracellular matrix proteins.…”
Section: Epidermal Construct On a Collagen Layermentioning
confidence: 90%
See 2 more Smart Citations
“…Our findings are in accordance with previous studies showing that the formation of basement membrane at the dermal-epidermal junction, as well as the synthesis of other matrices by dermal fibroblasts, requires the interactions between keratinocytes and dermal fibroblasts. [43][44][45]57 Although the basement membrane was absent in our constructs, basal keratinocytes expressed integrin b1 subunit and a2b1 integrin. Integrins are heterodimeric cellsurface glycoproteins that primarily mediate the attachment of basal keratinocyte to extracellular matrix proteins.…”
Section: Epidermal Construct On a Collagen Layermentioning
confidence: 90%
“…Within synthetic constructs, it was possible to identify cell layers comparable with those observed in natural skin; nevertheless, the number of the cell layers (4-6 layers, including basal cells) was lower than in natural skin and other models of bilayered skin equivalents. 43,45,51,52 The ultrastructure of the synthetic construct showed a typical structure in the basal stratum with the natural epidermis. 53 However, electron microscopy analysis revealed that the overall organization of these layers, as well as keratinocyte differentiation, was poorer than with natural epidermis, including the formation of junctional complexes, basement membrane, and keratinization.…”
Section: Epidermal Construct On a Collagen Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this characteristic of skin, monolayer cell culture models cannot fully recapitulate the functional complexity of human skin. Thus, tissue-engineered skin substitutes utilizing alternative skin scaffold approaches, such as 3-dimensional (3D) collagen matrices may represent more effective systems for skin research (24,25). In addition, tissue-engineered skin substitutes provide a novel platform for testing the effects and biological reactions of pharmacological agents on the assembly of tissuelike structures, and may be suitable for replacing some in vivo experiments and preliminary real human skin studies (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The cells with their characteristic round morphology are in active proliferation, as revealed by the presence of mitotic figures, until they organize in three-dimensional compact clusters. At this stage they were immuno-stained with anti-Cytokeratin, clon AE1/AE3, which reacts with most cytokeratins [36,37] allowing positive identification of keratinocytes inside the microcapsule. Moreover, when histological sections were immuno-stained with polyclonal anti-Vimentin, looking for the presence of fibroblasts, scarce reaction was verified, thereby indicating a predominant population of keratinocytes with meaningless presence of fibroblasts.…”
Section: Microencapsulated Keratinocytes Behaviormentioning
confidence: 99%